Extended blood stage sensitivity profiles of Plasmodium cynomolgi to doxycycline and tafenoquine, as a model for Plasmodium vivax - Christensen, Peter (2024)
Testing Plasmodium vivax antimicrobial sensitivity is limited to ex vivo schizont maturation assays, which preclude determining the IC50s of delayed action antimalarials such as doxycycline. Using Plasmodium cynomolgi as a model for P. vivax, we determined the physiologically significant delayed death effect induced by doxycycline [IC50(96 h), 1,401 ± 607 nM]. As expected, IC50(96 h) to chloroquine (20.4 nM), piperaquine (12.6 µM), and tafenoquine (1,424 nM) were not affected by extended exposure.